1995
DOI: 10.1007/bf00198904
|View full text |Cite
|
Sign up to set email alerts
|

Evidence against heterozygous coagulation factor V 1691 G?A mutation with resistance to activated protein C being a risk factor for coronary artery disease and myocardial infarction

Abstract: The aim of our study was to determine the prevalence of the factor V mutation (position 1691 G-->A) in patients with angiographically diagnosed coronary artery disease and myocardial infarction and, as a control, in blood donors. This mutation has already been proved to be the main genetic risk factor for venous thrombosis. In order to detect this mutation in exon 10 of the factor V gene we established a microtiter plate based hybridization assay for the specific detection of wild-type and mutant sequences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…Our data agree with these observations since this lower incidence may partly reflect the absence of the most important known cause of venous thrombophilia (the FVL mutation) in this ethnic group. The possibility that FVL might be a genetic risk factor for arterial thrombotic disease has been investigated in several studies, but with conflicting results (Prohaska et al, 1995;Kontula et al, 1995;van der Bom et al, 1996;Foley et al, 1997). However, a recent study demonstrated a clear relationship between the presence of FVL and increased predisposition for myocardial infarction in young women (Rosendaal et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Our data agree with these observations since this lower incidence may partly reflect the absence of the most important known cause of venous thrombophilia (the FVL mutation) in this ethnic group. The possibility that FVL might be a genetic risk factor for arterial thrombotic disease has been investigated in several studies, but with conflicting results (Prohaska et al, 1995;Kontula et al, 1995;van der Bom et al, 1996;Foley et al, 1997). However, a recent study demonstrated a clear relationship between the presence of FVL and increased predisposition for myocardial infarction in young women (Rosendaal et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] From those, 12 studies were excluded because no solid diagnostic criteria for myocardial infarction were used, [17][18][19][20] there was inadequate delineation of cases, 21,22 or there was an inadequate spectrum of cases, [11][12][13][14][15][16] leaving a total of 6 studies in the analysis.…”
Section: Factor V Leiden Mutationmentioning
confidence: 99%
“…Most studies on FVL and arterial thrombosis have demonstrated insignificant or borderline significant associations, some studies favoring a risk reduction in FVL carriers, [5][6][7][8][9][10][11][12][13][14][15][16] others an increase. The present study (1) estimated risk of thrombosis in atherosclerotic arteries (MI or IS) as well as risk of atherosclerosis without thrombosis (non-MI-ischemic heart disease [non-MI-IHD]) in FVL carriers, using a population-based study; (2) examined if FVL interacts with established cardiovascular risk factors in predicting MI, IS, and non-MI-IHD; and finally (3) systematically combined our data with previously published studies on FVL and risk of arterial thrombosis using meta-analyses.…”
Section: Introductionmentioning
confidence: 99%